Serum triglyceride levels are associated with recurrence in patients with acute hypertriglyceridemic pancreatitis - Guan, Langyi; Ding, Ling; Wan, Jianhua; Xia, Liang; He, Wenhua; Xiong, Huifang; Luo, Lingyu; Lu, Nonghua; Zhu, Yin (Frontiers in Medicine, 2023)
Aim To analyze the clinical profile of patients with acute hypertriglyceridemic pancreatitis (HTGP) and explore risk factors for recurrence. Methods A retrospective observational study was conducted in patients who experienced an attack of HTGP for the first time. Patients were followed untill the recurrence of acute pancreatitis (AP) or one year. The detailed clinical profile was compared between patients with or without recurrence. Multivariate logistic regression analysis was conducted to explore independent risk factors for recurrence. Results A total of 108 HTGP patients were included in this study with 73.1% being male, and the median age being 37 (interquartile range, IQR, 30.3-44.8) years. Recurrence occurred in 70 patients (64.8%). Compared with the nonrecurrent group, serum triglyceride (TG) levels before discharge (4.1 (2.8,6.3) mmol/L vs. 2.9 (2.2,4.2) mmol/L; p=0.002), at 1 month (3.7 (2.3,9.7) mmol/L vs. 2.0 (1.4,2.7) mmol/L; p=0.001), at 6 months (6.1 (3.1,13.1) mmol/L vs. 2.5 (1.1,3.5) mmol/L; p=0.003) and 12 months (9.6 (3.5,20.0) mmol/L vs. 2.7 (1.6,5.5) mmol/L; p=0.001) after discharge were higher in the recurrent group. Poor control of TG levels (TG>3.1 mmol/L) at the 1-month follow-up after discharge and a high Charlson’s Comorbidity Index score (≥ 2 points) increased the risk of recurrence of HTGP. Conclusions High TG levels during follow-up and Charlson’s Comorbidity Index score were independently associated with recurrence in patients with HTGP.